The Influence of Work Motivation and Incentives on Employee Productivity of PT.Lamipak Primula Indonesia - Fatimah Yusuf; Endang Muryani; Dwi Widi Hariyanto (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2024)
The study used quantitative methods and was conducted at PT Lamipak Primula Indonesia by using a research sample of 130 employees of PT Lamipak Primula Indonesia. This study aims to analyze the effect of Motivation and Insentife on Work Productivity at PT Lamipak Primula Indonesia, The results of this study indicate that work motivation does not have a significant effect on work productivity, while the incentive variable has a significant effect on work productivity positively. These findings indicate the importance of non-financial factors in motivating employees and increasing productivity.